Mental health interventions and services for vulnerable children and young people - Vostanis, Panos (Jessica Kingsley Pub., 2007)
This book provides a model which offers guidance on effective and appropriate therapeutic interventions and services for vulnerable children and young people (commonly children who have experienced trauma, abuse, domestic violence or neglect). By addressing practice, theory and policy, the book enables professionals working with vulnerable children to choose the right intervention for each individual child. Contributors examine best practice across the UK, the US and Europe and compile the findings in a way that can be incorporated into everyday practice. Mental Health Interventions and Servic.